PEMANFAATAN RHIZOBIUM UNTUK MENINGKATKAN PERTUMBUHAN SEMAI SENGON (Paraserianthes falcataria) PADA MEDIA TANAH BEKAS TAMBANG SEMEN - Ceng Asmarahman; Indra Gumay Febryano (Universitas Tanjungpura, 2012)
Ex-mining land use of cement was an alternative medium or planting medium, but this alternative was to meet the constraints of low soil fertility levels. Therefore, one way that could be attempted is creating suppressive soil in the form of applying biofertilizer such as rhizobium (Nitrogen Fixing Bakteria). Research methods used a complete randomized design. The first factor was the type of Rhizobium (control, Shinorhizobium sp (S8.4), Rhizobium sp (S10.3.1) which was inoculated on the plant Paraserianthes falcataria. Planting medium used was sterilized soil from ex-cement mining land. The results of rhizobium inoculation on plants showed different effectiveness in enhancing the growth of seedlings. Duncan test results of the influence of a single factor BFN showed Shinorhizobium sp (S8.4) could be associated with P. falcataria, to improved seedling growth and able to gave growth response better when compared with treatment of Rhizobium sp (S10.3.1) and control at variable observations on seedling diameters (1.65 mm), number of leaves (10.9 pieces), N absorption (2.10 g/plant) and P absorption (0.16 g/plant). Keywords: Paraserianthes falcataria, rhizobium, bacteria, seedlings, soil media of ex - cement mining